Effects of dietary inclusion of microalgae Arthrospira platensis on the growth performance and carcass quality in Japanese quails (Coturnix japonica temminck & schlegel) - Danny Cheong, Swee Weng (2014)
In recent years, quail meat has been gaining much popularity among consumers in Malaysia and quail rearing is expected to increase to meet the high demand for local and international market. Although a series of researches had been carried out to determine the optimum level of A. platensis inclusion for fast growing commercial broiler and layer chicken diet but not in Japanese quail diet. Hence, two experiments were conducted to study the effects of feeding microalgae A. platensis on the growth performance and carcass quality of Japanese quails. In the first experiment, three hundred 14 days old quails were randomly subjected to 5 treatments consisted of basal diet-control (C), diet with 1% A. platensis inclusion, diet with 2% A. platensis inclusion, diet with 4% A. platensis inclusion and diet with 8% A. platensis inclusion. Each treatment was replicated three times, consisting of 20 birds. The feeding experiment period lasted for 21 days. Basal diet was based on corn and soybean meal. In the first experiment, dietary of A. platensis inclusion significantly improved weekly body weight gain (BWG) and feed conversion ratio (FCR) in quails. Also, Mortality rate (MR), carcass yield, meat colour values and meat tenderness were significantly improved by A. platensis diet. These results concluded that A. platensis was suitable as a supplement in quails’ feed for improving growth performance and carcass quality. In this experiment, 4% A. platensis inclusion was identified to be the most suitable level considering most parameters showed positive observation. In the second experiment, three hundred 14 days old quails were randomly allocated into 5 dietary treatment groups, consisting basal diet-control group, groups with 4% A. platensis diet at different starting age of 15 days old, 22 days old and 28 days old and group fed with commercial diet. Each treatment was replicated three times, consisting 20 birds. The feeding experiment lasted for 21 days. Body weight gains (BWG), feed conversion ratio (FCR) and mortality rate (MR) were significantly improved from the time of A. platensis inclusion into diet. Also, carcass yield, meat colour test and meat tenderness were also significantly improved when introduced A. platensis diet at earlier growing stage. The results demonstrated that at starting age from day 15 to as later as day 22 were found to be the best time of A. platensis inclusion into quail diet to achieve positive growth performance and improve carcass quality.